2017
DOI: 10.1111/papr.12582
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Root Ganglion Stimulation for Complex Regional Pain Syndrome (CRPS) Recurrence after Amputation for CRPS, and Failure of Conventional Spinal Cord Stimulation

Abstract: Background: Limb amputation is sometimes being performed in long-standing complex regional pain syndrome (CRPS), although little evidence is available guiding management decisions, including how CRPS recurrence should be managed. Methods: This report details the management of a young soldier with CRPS recurrence 2 years after midtibial amputation for CRPS. Results: Conventional spinal cord stimulation did not achieve paraesthetic coverage, or pain relief in the stump, whereas L4 dorsal root ganglion stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…DRG stimulation is a logical option for treatment of phantom limb pain (PLP); however, publication on the topic has been limited to date [10,38,39]. Postamputation patients by definition have a nerve injury (neurotomy), and many suffer chronic stump, residual limb, and/or phantom pain.…”
Section: Methods/resultsmentioning
confidence: 99%
“…DRG stimulation is a logical option for treatment of phantom limb pain (PLP); however, publication on the topic has been limited to date [10,38,39]. Postamputation patients by definition have a nerve injury (neurotomy), and many suffer chronic stump, residual limb, and/or phantom pain.…”
Section: Methods/resultsmentioning
confidence: 99%
“…Several studies showed good results using DRGS in the treatment of CRPS (21,29). In a study with CRPS and the failure of conventional SCS, DRGS provided sufficient pain relief (30). Eleven patients diagnosed with uni-or bilateral lower-extremity CRPS, were recruited in a prospective case series as part of a larger study involving chronic pain of heterogeneous etiologies.…”
Section: Crpsmentioning
confidence: 99%
“…The remaining three case reports included a total of 17 participants who have previously failed various treatment; they measured pain intensity by numeric rating scale (NRS); and all participants showed >50% pain reduction at all follow-up time points (Table 1). 3436…”
Section: Resultsmentioning
confidence: 99%